Insights from the Newborn Screening Program for Very Long-Chain Acyl-CoA Dehydrogenase (VLCAD) Deficiency in Kuwait - Hind Alsharhan; Amir A. Ahmed; Marwa Abdullah; Moudhi Almaie; Makia J. Marafie; Ibrahim Sulaiman; Reem M. Elshafie; Ahmad Alahmad; Asma Alshammari; Parakkal Xavier Cyril; Usama M. Elkazzaz; Samia M. Ibrahim; et al. (International Journal of Neonatal Screening)
Newborn screening for very long-chain acyl-CoA dehydrogenase (VLCAD) deficiency in Kuwait was initiated in October 2014. Over a 7-year period (January 2015 to December 2021), 43 newborns were diagnosed with VLCAD deficiency out of 356,819 screened, corresponding to an incidence of 1:8290 and 1:5405 among only Kuwaiti newborns. This study represents the first comprehensive review of newborn screening for VLCAD deficiency in Kuwait. The screening process begins with the detection of elevated blood C14:1 levels in dried blood spots, followed by confirmatory testing using dried blood spots acylcarnitine profiling, with or without molecular testing. Furthermore, this study demonstrates that incorporating the C14:1/C2 ratio as a supplementary marker in first-tier testing alongside C14:1 improves the positive predictive value (PPV) of the current newborn screening for VLCAD deficiency. Adding molecular genetic testing for known VLCAD variants as a second-tier strategy to the national program is also recommended to further enhance specificity and improve PPV. Our findings provide evidence that the expanded newborn screening program in Kuwait has successfully facilitated the early detection of VLCAD deficiency, preventing death and disability in affected infants.